Capturing Swiss economic confidence - Philipp Wegmueller; Christian Glocker (Swiss Journal of Economics and Statistics, 2024)
Abstract Survey data can offer timely information on the current state of the economy and its short-term outlook. In this paper, we propose a “Swiss Economic Confidence Index” (SEC). This is a monthly indicator based on aggregating a selection of individual survey indicators, which we show to have favorable leading properties. Applying simple criteria, we select those surveys from a set of currently more than 250 sentiment indicators. We show that the SEC index provides useful signals on GDP growth in a number of real-time out-of-sample forecasting exercises.